Synthesis and Crystal Structure of 2,2-Dimethyl-5-((2-phenylhydrazinyl)methylene)-1,3-dioxane-4,6-dione - Zeng, Wu-Lan; Liu, Hui-Lian (Asian Journal of Chemistry, 2014)
A new Meldrum's acid compound 2,2-dimethyl-5-((2-phenylhydrazinyl)methylene)-1,3-dioxane-4,6-dione was prepared by 2,2-dimethyl-1,3-dioxane-4,6-dione, methylorthoformate and phenylhydrazine in ethanol and its crystal structure was determined by X-ray crystallographic techniques. It crystallizes in Triclinic, space group P-1 with a = 13.514 (3) Å, b = 13.550 (3) Å, c = 13.599 (3) Å, a = 104.01 (3)°, b = 103.90 (3)°, g = 103.91 (3)°, C13H14N2O4, Mr = 262.26, V = 2224.4 (11) Å3, Z = 6, Dc = 1.175 g/cm3, F (000) = 828, μ = 0.088 mm-1. The 1,3-dioxane ring is in a screw-boat conformation. The crystal structure is stabilized by weak intermolecular C–H···O and N–H···O.